Novel Poly-Arginine Peptide R18D Reduces α-Synuclein Aggregation and Uptake of α-Synuclein Seeds in Cortical Neurons - Emma C. Robinson; Anastazja M. Gorecki; Samuel R. Pesce; Vaishali Bagda; Ryan S. Anderton; Bruno P. Meloni (Biomedicines)
Background/Objectives: The role of α-synuclein (α-syn) pathology in Parkinson’s disease (PD) is well established; however, effective therapies remain elusive. Two mechanisms central to PD neurodegeneration are the intracellular aggregation of misfolded α-syn and the uptake of α-syn aggregates into neurons. Cationic arginine-rich peptides (CARPs) are an emerging class of molecule with multiple neuroprotective mechanisms of action, including protein stabilisation. This study characterised both intracellular α-syn aggregation and α-syn uptake in cortical neurons in vitro. Thereafter, this study examined the therapeutic potential of the neuroprotective CARP, R18D (18-mer of D-arginine), to prevent the aforementioned PD pathogenic processes through a cell-free thioflavin-T (ThT) assay and in cortical neurons. Methods: To induce intracellular α-syn aggregation, rat primary cortical neurons were exposed to α-syn seed (0.14 μM) for 2 h to allow uptake of the protein, followed by R18D treatment (0.0625, 0.125, 0.25, 0.5 μM), and a subsequent measurement of α-syn aggregates 48 h later using a homogenous time-resolved fluorescence (HTRF) assay. To assess neuronal uptake, α-syn seeds were covalently labelled with an Alexa-Fluor 488 fluorescent tag, pre-incubated with R18D (0.125, 0.25, 0.5 μM), and then exposed to cortical neurons for 24 h and assessed via confocal microscopy. Results: It was demonstrated that R18D significantly reduced both intracellular α-syn aggregation and α-syn seed uptake in neurons by 37.8% and 77.7%, respectively. Also, R18D reduced the aggregation of α-syn monomers in the cell-free assay. Conclusions: These findings highlight the therapeutic potential of R18D to inhibit key α-syn pathological processes and PD progression.